IMPLEMENTASI METODE TALAQQI DALAM PEMBELAJARAN TAHFIZH DI TAMAN PENDIDIKAN QUR’AN INSAN MULIA JAKARTA - Reti Riset; Dian Nurul Husna; Fitri Nur Alfiyah; Rizal Arsyad (LP2M JAMIAT KHEIR, 2026)
This study examines the application of the talaqqi method in tahfizh classes at the Taman Pendidikan Qur'an (TPQ) Insan Mulia Mushala Darul Falah, Meruya Utara Branch, which consists of students from diverse age groups. These age differences present specific challenges, particularly regarding the loss of focus among younger students and the management of waiting times during memorization submissions. Using a descriptive qualitative method, this research integrates Edward Thorndike's and Vygotsky's theories of learning psychology, aligned with Imam Al-Ghazali's Islamic educational principles. The findings indicate that the talaqqi and musyafahah methods serve as quality control to ensure the accuracy of students' tajwid and makhraj. The application of Thorndike's theory helps strengthen memory retention through routine repetition, while Al-Ghazali's perspective emphasizes the importance of maintaining spiritual purity from digital distractions (gadgets). This study concludes that the key to successful talaqqi within heterogeneous age classes at this institution lies in effective queue management to prevent learning burnout and maintain students' enthusiasm for memorization